Biodiversity of the ant fauna in different soil uses in North Mato Grosso - Corassa, Janaina De Nadai; Faixo, João Gabriel; Andrade Neto, Valmir Rodrigues; Santos, Ivone Beatryz (Federal University of Piauí, 2015)
This work aimed to evaluate the impact of the ant fauna in two areas for the cultivation of monocultures, compared to the native forest environment, applied to the North Mato Grosso. For this three environments were analyzed: maize crop, the planting of eucalyptus and native Forest. 6 collections were performed in each of the three environments, each composed of 15 samples collected from 1m ² of litter, totaling 90 samples per environment. The work occurred in the period from February to June 2011, the municipalities of Lucas do Rio Verde-MT and MT-Vera. The samples were submitted to Winkler extractor for 72 hours for analysis and quantification of existing species. It was quantified the number of species in each environment as well as the diversity index by the method of Shannon-Wiener (H ‘). He collected a total of 29 species of formicídeos, divided into 16 genera, 10 tribes and 5 subfamilies, among subfamilies, with the largest number of species was Mirmicinae, already among the environments, what had the highest species richness was the native forest (26), followed by the planting of eucalyptus (8) and maize crop(6). The native forest had the highest diversity index Shannon-Wiener (0.47), followed by eucalyptus plantations (0.35) and maize crop (0.23). For the analysis of sample sufficiency, the number of samples was not enough to characterize the environment in relation to the species in it, because the curve for the number of species has not stabilized. It was shown the role of the genus Pheidole bioindicator, which is related to the environment preserved, and that the replacement of native vegetation has an impaction the local ant fauna, reducing the number of species in the area, a fact related to the decrease of the structural complexity of the environment.